X linked Charcot-Marie-Tooth disease and multiple sclerosis: emerging evidence for an association. Issue 2 (8th September 2018) - Koutsis, Georgios; Breza, Marianthi; Velonakis, Georgios; Tzartos, John; Kasselimis, Dimitrios; Kartanou, Chrisoula; Karavasilis, Efstratios; Tzanetakos, Dimitrios; Anagnostouli, Maria; Andreadou, Elisavet; Evangelopoulos, Maria-Eleftheria; Kilidireas, Constantinos; et al.
Abstract : Objective: X linked Charcot-Marie-Tooth disease (CMTX) is a hereditary neuropathy caused by mutations in GJB1 coding for connexin-32, a gap junction protein expressed in Schwann cells, but also found in oligodendrocytes. Four patients with CMTX developing central nervous system (CNS) demyelination compatible with multiple sclerosis (MS) have been individually published. We presently sought to systematically investigate the relationship between CMTX and MS. Methods: Over 20 years, 70 consecutive patients (36 men) with GJB1 mutations were identified at our Neurogenetics Unit, Athens, Greece, and assessed for clinical features suggestive of MS. Additionally, 18 patients with CMTX without CNS symptoms and 18 matched controls underwent brain MRI to investigate incidental findings. Serum from patients with CMTX and MS was tested for CNS immunoreactivity. Results: We identified three patients with CMTX who developed clinical features suggestive of inflammatory CNS demyelination fulfilling MS diagnostic criteria. The resulting 20-year MS incidence (4.3%) differed significantly from the highest background 20-year MS incidence ever reported from Greece (p=0.00039). The search for incidental brain MRI findings identified two CMTX cases (11%) with lesions suggestive of focal demyelination compared with 0 control. Moreover, 10 cases in the CMTX cohort had hyperintensity in the splenium of the corpus callosum compared with 0 control (p=0.0002). No specific CNS-reactive humoral factors were identified in patients with CMTX and MS. Conclusions: We have demonstrated a higher than expected frequency of MS in patients with CMTX and identified incidental focal demyelinating lesions on brain MRI in patients with CMTX without CNS symptoms. This provides circumstantial evidence for GJB1 mutations acting as a possible MS risk factor.